Inhibitory Effect of Biotransformed-Fucoidan on the Differentiation of Osteoclasts Induced by Receptor for Activation of Nuclear Factor-κB Ligand - Park, Bobae; Yu, Sun Nyoung; Kim, Sang-Hun; Lee, Junwon; Choi, Sung Jong; Chang, Jeong Hyun; Yang, Eun Ju; Kim, Kwang-Youn; Ahn, Soon-Cheol (Journal of microbiology and biotechnology, 2022)
Bone homeostasis is regulated by constant remodeling through osteogenesis by osteoblasts and osteolysis by osteoclasts and osteoporosis can be provoked when this balance is broken. Present pharmaceutical treatments for osteoporosis have harmful side effects and thus, our goal was to develop therapeutics from intrisincally safe natural products. Fucoidan is a polysaccharide extracted from many species of brown seaweed, with valuable pharmaceutical activities. To intensify the effect of fucoidan on bone homeostasis, we hydrolyzed fucoidan using AMG, Pectinex and Viscozyme. Of these, fucoidan biotransformed by Pectinex (Fu/Pec) powerfully inhibited the induction of tartrate-resistant acid phosphatase (TRAP) activity in osteoclasts differentiated from bone marrow macrophages (BMMs) by the receptor for activation of nuclear factor-κB ligand (RANKL). To investigate potential of lower molecular weight fucoidan it was separated into >300 kDa, 50-300 kDa, and <50 kDa Fu/Pec fractions by ultrafiltration system. The effects of these fractions on TRAP and alkaline phosphatase (ALP) activities were then examined in differentiated osteoclasts and MC3T3-E1 osteoblasts, respectively. Interestingly, 50-300 kDa Fu/Pec suppressed RANKL-induced osteoclasts differentiation from BMMs but did not synergistically enhance osteoblasts differentiation induced by osteogenic agents. In addition, this fraction inhibited the expressions of NFATc1, TRAP, OSCAR, and RANK, which are all key transcriptional factors involved in osteoclast differentiation, and those of Src, c-Fos and Mitf, as determined by RT-PCR. In conclusion, enzymatically low-molecularized 50-300 kDa Fu/Pec suppressed TRAP by downregulating RANKL-related signaling, contributing to the inhibition of osteoclasts differentiation, and represented a potential means of inducing bone remodeling in the background of osteoporosis.